The ghost and the stolen tears - Coyle, Cleo (Kimberly, Alice. Haunted bookshop mystery., 2022)
Norma is a modern-day nomad. Living out of her van and teardrop trailer, she revels in self-reliance, solitude, and reading in the glorious peace of nature. Jovial, wise, and scrupulously honest, she's become an uplifting presence in the little town of Quindicott, Rhode Island, where bookseller Pen is thankful to have her part-time help. But it's Norma's other job, working as a housekeeper at the Finch Inn, that gets her into terrible trouble. Norma is accused of stealing jewels from a guest's room: the legendary Valentino Teardrops, an antique necklace and earring set, inherited by a young socialite. Pen doesn't believe Norma is guilty of the crime--though the evidence is distressingly strong. And when the spirited Norma vanishes before her arrest, Pen turns to another spirit... Jack Shepard, PI, may have been gunned down decades ago, but his memory hasn't been ghosted. Back in the 1940s, those same Valentino Teardrops starred in a bizarre case of betrayal and murder. From the look of things, history is about to repeat. Now Jack is back on the job, and Pen is eternally grateful.